2012
DOI: 10.1521/ijgp.2012.62.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Group CBT for Early Psychosis—Are There Still Benefits One Year Later?

Abstract: Our team recently conducted a randomized controlled trial comparing group cognitive behavior therapy for psychosis (CBTp) to group social skills training for symptom management and a wait-list control group, for early psychosis. The results at post-therapy and six months provided considerable empirical support for the efficacy of the group CBTp. The results of the one-year follow-up are described here. Given the high attrition rates, mostly in the comparison and control conditions, imputations were not possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
2
21
0
1
Order By: Relevance
“…The inclusion of non-verbal therapies and more precise statistical techniques may account for this difference. Furthermore, results from this review are not consistent with the notion that group processes can be effective in aiding the restructuring of false beliefs around delusions or hallucinations [15,71] in the treatment of positive symptoms [20,23,26]. As suggested by Wykes et al [7], it might be difficult for therapists to flexibly respond to a wide variety of individual therapeutic needs when addressing positive symptoms in groups.…”
Section: Discussionmentioning
confidence: 66%
“…The inclusion of non-verbal therapies and more precise statistical techniques may account for this difference. Furthermore, results from this review are not consistent with the notion that group processes can be effective in aiding the restructuring of false beliefs around delusions or hallucinations [15,71] in the treatment of positive symptoms [20,23,26]. As suggested by Wykes et al [7], it might be difficult for therapists to flexibly respond to a wide variety of individual therapeutic needs when addressing positive symptoms in groups.…”
Section: Discussionmentioning
confidence: 66%
“…They found that people in both active treatment groups (CBTp and SST) had significantly improved scores on the BPRS negative symptom scale at post-treatment, but not at the six-month follow-up. At the one-year follow-up, people who received CBTp tended ( p = 0.06) to maintain the improvements in negative symptoms (Lecomte et al, 2012). …”
Section: Social Skills Trainingmentioning
confidence: 99%
“…Of these, 22 were RCTs that reported on negative symptom outcomes (see Table 1). Sixteen of these evaluated individual CBT, four evaluated group CBT, one evaluated a combination of individual and group CBT, and one evaluated group CBT in comparison to social skills training (SST; Lecomte et al, 2008; Lecomte, Leclerc, & Wykes, 2012), which we discuss in the SST section.…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…38 Entre los pocos estudios que evalúan la efectividad de esta intervención en los síntomas negativos se encuentra el de Valencia et al 29 quienes reportan una disminución de la sintomatología negativa mediante programas de aprendizaje de habilidades sociales con duración de seis meses a un año. Por su parte, Lecomte, Leclerc y Wykes 39 encontraron en su estudio que a pesar de que existió una disminución de la gravedad de los síntomas negativos al momento del postratamiento, estos resultados no se mantuvieron en el seguimiento a 12 meses.…”
unclassified